Synthesis and Characterization of Some Four Coordinated Zinc(II) and Mercury(II) Complexes - Montazerozohori, M.; Nouroozi, V.; Hashemi, S.; Kazemi, Z.; Joohari, S.; Musavi, S.A. (Asian Journal of Chemistry, 2011)
Several new symmetrical bidentate Schiff base ligands (L1= N,N-bis(4-chlorobenzylidene)ethane- 1,2-diamine, L2= N,N-bis(3-nitrobenzylidene)ethane-1,2-diamine and L3= N,N-bis(4- nitrobenzylidene)ethane-1,2-diamine and their zinc(II) and mercury(II) complexes with general formula MLX2 in which X= Cl-, Br- and I- and M=Hg(II) and Zn(II) have been prepared and characterized by elemental analysis, 1H NMR, 13C NMR, Fourier transform-infrared and ultraviolet- visible spectra and molar conductance. All compounds are non-electrolytes in dimethylformamide. The molar conductance and spectral properties indicate coordination of halides ions to metal in pseudo-tetrahedral geometry.